Exosome Therapy in Stress Urinary Incontinence: A Comprehensive Literature Review - Manouchehr Nasrollahzadeh Saravi; Mahdi Mohseni; Iman Menbari Oskouie; Jafar Razavi; Ernesto Delgado Cidranes; Masoumeh Majidi Zolbin (Biomedicines)
Stress urinary incontinence (SUI) is characterized by the involuntary leakage of urine when bladder pressure exceeds urethral closing pressure during routine activities such as physical exertion, coughing, exercise, or sneezing. SUI is the most prevalent form of urinary incontinence, with a reported prevalence ranging from 10% to 70%, and its incidence increases with age. As the global population continues to age, the prevalence and clinical significance of SUI are expected to rise accordingly. The pathophysiology of SUI is primarily driven by two mechanisms: urethral hypermobility, resulting from compromised supporting structures, and intrinsic urethral sphincter deficiency, characterized by the deterioration of urethral mucosa and muscle tone. Current treatment options for SUI include conservative management strategies, which heavily rely on patient adherence and are associated with high recurrence rates, and surgical interventions, such as sling procedures, which offer effective solutions but are costly and carry the risk of adverse side effects. These limitations highlight the urgent need for more effective and comprehensive treatment modalities. Exosomes, nano-sized (30–150 nm) extracellular vesicles secreted by nearly all cell types, have emerged as a novel therapeutic option due to their regenerative, anti-fibrotic, pro-angiogenic, anti-apoptotic, anti-inflammatory, and anti-hypoxic properties. These biological functions position exosomes as a promising alternative to conventional therapies for SUI. Exosome therapy has the potential to enhance tissue regeneration, restore urethral function, and repair nerve and muscle damage, thereby reducing symptom burden and improving patients’ quality of life. Additionally, exosome-based treatments could offer a less invasive alternative to surgery, potentially decreasing the need for repeated interventions and minimizing complications associated with current procedures. In this literature review, we critically assess the current state of research on the potential use of exosomes in treating SUI, highlighting their therapeutic mechanisms and potential clinical benefits.